PERTANGGUGNGJAWABAN PELAKU TINDAK PIDANA PEMALSUAN DAN PENGEDARA UANG PALSU DITINJAU DARI PERSFEKTIF HUKUM POSITIF - gios, gios adhyaksa (Yuriska: Jurnal Ilmiah Hukum, 2022)
The criminal act of currency counterfeiting is a crime that attacks public confidence in the authenticity of currency, therefore the truth of the currency value must be guaranteed from counterfeiting. Based on the description, the objectives are to find out how the current regulation of counterfeiting and circulation of counterfeit money is, and to find out how to enforce the law against the perpetrators of counterfeiting and circulating counterfeit money. The method used by the author in this study is a normative juridical approach using primary and secondary data collection techniques and data collection tools used through interviews and document studies. The results of this study with the theme of research on the responsibility of the perpetrators of the crime of counterfeiting and circulating counterfeit money. From a positive legal perspective, counterfeiting and circulation of counterfeit money carried out by perpetrators as makers and dealers must have fulfilled the elements in the formulation of Articles 244 and 245 of the Criminal Code. Law enforcement against perpetrators of counterfeiting and circulation of counterfeit money is carried out by law enforcement officers starting from the police, prosecutors and courts in the stages of the criminal justice system in Indonesia which aims to impose penalties on perpetrators of criminal acts of counterfeiting money and prevent and cope with people becoming victims of counterfeiting money, resolving criminal cases and create a deterrent effect for perpetrators of criminal acts of counterfeiting and circulating counterfeit money.